2021
DOI: 10.1088/1755-1315/735/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different broiler flooring systems on surface temperature, air quality and carcass characters of broilers

Abstract: The present study investigated the use of perforated plastic floors with different heights in the broiler performance, surface temperature, air quality, and carcass characters of broilers. Three hundred sixty-seven day-old unsexed chicks randomly divided into 4 groups: control reared on sawdust litter in others used, plastic floors with different heights (5, 10 and 15) cm, for 2nd, 3rd and 4th treatment respectively. The first treatment (sawdust) showed significantly (P < 0.05) increase in body surface temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…The perforated floor wire floor has a positive effect on the health and behavior of domestic birds, which is evidenced by indicators of welfare without a decrease in indicators of productive performance [15]. The results showed that raising broiler chickens on the wire floor did not record significant differences in most of the productive traits at the age of 21 and 38 days , We agree with Al-Nasiri [7,8] as well as the relative weight of abdominal and liver fat, The results did not agree with [4]. nor did we find differences in the relative weight of the Bursa of fabricius, Thymus gland [4].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The perforated floor wire floor has a positive effect on the health and behavior of domestic birds, which is evidenced by indicators of welfare without a decrease in indicators of productive performance [15]. The results showed that raising broiler chickens on the wire floor did not record significant differences in most of the productive traits at the age of 21 and 38 days , We agree with Al-Nasiri [7,8] as well as the relative weight of abdominal and liver fat, The results did not agree with [4]. nor did we find differences in the relative weight of the Bursa of fabricius, Thymus gland [4].…”
Section: Discussionsupporting
confidence: 79%
“…The effect of the floor type on the on serum Antioxidant activity. The results of Table (8) shows that there are no significant differences between groups in thyroid hormones, melatonin hormone and growth hormone in the serum of broiler chickens. Table 8.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations